HLA Allele Frequencies in 5802 Koreans: Varied Allele Types Associated with SJS/TEN According to Culprit Drugs - Park, Hye Jung; Kim, Young Joo; Kim, Dong Hyun; Kim, Junho; Park, Kyung Hee; Park, Jung-Won; Lee, Jae-Hyun (Yonsei medical journal, 2016)
Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are very serious forms of drug-induced cutaneous adverse reaction. SJS/TEN induced by certain drug is well known to be associated with some human leukocyte antigen (HLA) gene type. We aimed to explore HLA allele frequencies and their association with SJS/TEN according to culprit drugs in Korea. We enrolled 5802 subjects who had results of HLA typing test from August 2005 to July 2014. Total 28 SJS/TEN patients were categorized based on culprit drugs (allopurinol, lamotrigine, carbamazepine) and identified the presence of HLA-B*58:01, HLA-B*44:03, HLA-B*15:02, and HLA-A*31:01. HLA-A*24:02 (20.5%), HLA-B*44:03 (10.0%), and HLA-Cw*01:02 (17.1%) were the most frequent type in HLA-A, -B, and -C genes, respectively. Allele frequencies of HLA-B*58:01, HLA-B*44:03, HLA-A*31:01, and HLA-B*15:02 were 7.0%, 10.0%, 5.0%, and 0.3%, respectively. In 958 allopurinol users, 9 subjects (0.9%) were diagnosed with SJS/TEN. Among them, 8 subjects possessed HLA-B*58:01 allele. SJS/TEN induced by allopurinol was more frequently developed in subjects with HLA-B*58:01 than in subjects without it [odds ratio: 57.4; confidence interval (CI) 7.12-463.50; p<0.001]. Allopurinol treatment, based on screening by HLA-B*58:01 genotyping, could be more cost-effective than that not based on screening. HLA-B*44:03 may be associated with lamotrigine-induced SJS/TEN (odds ratio: 12.75; CI 1.03-157.14; p=0.053). Among carbamazepine users, only two patients experienced SJS/TEN and possessed neither HLA-B*15:02 nor HLA-A*31:03. HLA gene frequencies varied in Korea. Screening of HLA-B*58:01 before the use of allopurinol might be needed to anticipate probability of SJS/TEN.